Geological Storage Of Carbon Dioxide (Co2) : Geoscience, Technologies, Environmental Aspects And Legal Frameworks. - Gluyas, J.; Mathias, S.; ScienceDirect eBooks (Burlington : Elsevier Science, 2013)
Geological storage and sequestration of carbon dioxide, in saline aquifers, depleted oil and gas fields or unminable coal seams, represents one of the most important processes for reducing humankind's emissions of greenhouse gases. Geological storage of carbon dioxide (CO2) reviews the techniques and wider implications of carbon dioxide capture and storage (CCS). Part one provides an overview of the fundamentals of the geological storage of CO2. Chapters discuss anthropogenic climate change and the role of CCS, the modelling of storage capacity, injectivity, migration and trapping of Carbon.
Fundamentals of geological storage of CO2 -- Environmental, social and regulatory aspects -- Case studies.
Print version record.
Includes index.
English.
Elsevier
Keywords: Geological carbon sequestration; TECHNOLOGY & ENGINEERING -- Environmental -- General; Geological carbon sequestration; Electronic books